2012
DOI: 10.1038/bmt.2012.3
|View full text |Cite
|
Sign up to set email alerts
|

The increase from 2.5 to 5 mg/kg of rabbit anti-thymocyte-globulin dose in reduced intensity conditioning reduces acute and chronic GVHD for patients with myeloid malignancies undergoing allo-SCT

Abstract: We previously reported that reduced intensity conditioning (RIC) regimen with fludarabine, BU and 2.5 mg/kg of rabbit anti-thymocyte globulin (r-ATG) was effective but associated with a high rate of acute and chronic GVHD. Therefore, we increased the dose of r-ATG to 5 mg/kg. In this report, we analyzed 87 patients with AML or myelodysplastic syndrome (MDS) undergoing allo-SCT from an HLA-identical sibling donor from 2000 to 2010. RIC consisted of fludarabine, BU and r-ATG 2.5 mg/kg on 1 day (r-ATG1; n=53) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 43 publications
8
50
1
Order By: Relevance
“…In this particular setting, the comparison of ATG and CsA GVHD prophylaxis to prophylaxis not containing ATG showed that the use of ATG was not linked to a higher risk of relapse in patients with equivalent cytogenetic risks. Most of the patients in this study had received thymoglobulin at a dose <6 mg/kg, and these results are consistent with the previously reported preserved GVL effect in patients treated with relatively reduced doses of ATG, [12][13][14] in contrast with doses >10 mg/kg. 3 As previously described, 11,12 our study confirms a protective effect of ATG against chronic GVHD.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In this particular setting, the comparison of ATG and CsA GVHD prophylaxis to prophylaxis not containing ATG showed that the use of ATG was not linked to a higher risk of relapse in patients with equivalent cytogenetic risks. Most of the patients in this study had received thymoglobulin at a dose <6 mg/kg, and these results are consistent with the previously reported preserved GVL effect in patients treated with relatively reduced doses of ATG, [12][13][14] in contrast with doses >10 mg/kg. 3 As previously described, 11,12 our study confirms a protective effect of ATG against chronic GVHD.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, two recent studies reported that GVHD prophylaxis with a reduced dose of ATG of 2.5 mg/kg versus 5 mg/kg in FluivBu2 RIC allogeneic HSCT with peripheral blood stem cells from matched related or unrelated donors was associated with an increased risk of acute and chronic GVHD. 13,14 Collectively, these data confirm that the optimal dose of thymoglobulin in the Flu-ivBu2 RIC regimen is about 5 mg/kg.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…20 ATG did not impact the 2-year CI of relapse in our study, which differs from the CIBMTR one in regard to patients' age (only 55 years and older), stem cell source (only PBSC), disease type and status (only AML in CR1), and donor compatibility (only matched donor). However, our results are in accordance with earlier report by other smaller studies, [21][22][23] as well as to a recent publication by our group on 1250 adult patients with de novo AML in CR1 given PBSC from HLA-identical siblings after chemotherapy-based RIC regimen, where the use of ATG and the use of alemtuzumab were each associated with a lower risk of chronic GVHD, but a similar risk of relapse. 24 Because of the selection criteria (only patients 8/8 matched were considered), we were unable to assess the impact of mismatches on the risk of chronic GvHD and eventually NRM.…”
Section: Discussionsupporting
confidence: 93%